Genetic studies of incubation behaviour and Mendelian traits in chickens - Basheer, Atia (The University of Edinburgh, 2013)
Finding the genes that underlie variation in production and developmental traits has important economic applications. Incubation behaviour represents a loss of production in conventional breeds of chicken adapted to local conditions and was what motivated this thesis. The Mendelian traits of comb type, crest, Silkie and normal feathers, feathered leg, fibromelanosis, comb colour, skin and shank colour, feather colour and patterns are of interest because of the insight they give to genes and development and were also investigated in the thesis. We used White Leghorn and Silkie lines of chicken to detect the genetic loci controlling incubation behaviour and Mendelian traits using linkage based analysis in an F2 cross. The evidence for QTL affecting incubation status over the whole period on chromosome 5 was strong (P<0.05). After the addition of 218 new informative SNP markers across the genome including chromosome 5 the 95% confidence interval spanned a region around 45 cM having previously been 95 cM. Three other suggestive QTL for incubation status were found after the addition of SNP markers on chromosome 1, 18, 19, E22C19W28 at 70, 0, 1 and 13cM respectively. The mode of action of the incubation status QTL indicates that the White Leghorn allele was either promoting incubation behaviour or that heterozygotes have performance that exceeds the homozygotes except the QTL on chromosome 1 where the Silkie allele is promoting incubation behaviour as might be expected. A highly significant QTL (P<0.01) for early incubation behaviour (25-30 weeks) was found on chromosome 8 at 18 cM. This QTL has an additive effect with the possession of a Silkie allele increasing the likelihood of incubation behaviour. Other suggestive QTL for early incubation behaviour were found on chromosome 26 and 1 at 0 and 66cM respectively. For Mendelian traits, genome wide significant (P<0.01) genetic loci for comb type, crest type and feather type was found on chromosome 7 at 77cM, linkage group E22C19W28 at 7cM and on chromosome 3 at 169cM respectively. Significant genetic loci (P<0.01) for leg colour and skin colour were found on chromosome 20 at 56cM and 60cM respectively. In the present study, loci for all feather patterns were found on E22C19W28 even after removing animals carrying the dominant white alleles, suggesting dominant white or another allele at the locus was still influential. Comb type and incubation behaviour were investigated at the gene level. Thyroid stimulating hormone receptor (TSHR) is believed to be involved in the process of domestication and was found at the peak position of the most significant QTL on chromosome 5 for incubation behaviour. Functional exploration of Wnt genes as a candidate gene for comb type was investigated by in-situ hybridization in Silkie and White Leghorn embryos. The Wnt6 gene showed expression in the region of the presumptive comb development of embryos. In conclusion, for the first time genetic loci that explain maternal behaviour have been described. The coincidence of the incubation behaviour locus on chromosome 5 with the site of the strongest selective sweep in poultry, the TSHR, and the coincidence of QTL on chromosome 1 and 8 with thyroid hormone activity it would appear that the thyrotrophic axis may be critical to the loss of incubation behaviour and improved reproductive performance with domestication. Further analysis of these loci should be able to produce markers that can reduce the propensity for birds to incubate. Comb type marker might allow introgression of this trait to prevent comb damage in commercial hens.
Keywords: incubation behaviour; morphological traits